Absence of pathogenic viruses in COVID‐19 convalescent plasma. Issue 1 (3rd November 2022) - Kandathil, Abraham J.; Benner, Sarah E.; Bloch, Evan M.; Shrestha, Ruchee; Ajayi, Olivia; Zhu, Xianming; Caturegli, Patrizio P.; Shoham, Shmuel; Sullivan, David; Gebo, Kelly; Quinn, Thomas C.; Casadevall, Arturo; et al.
Abstract: Background: It is important to maintain the safety of blood products by avoiding the transfusion of units with known and novel viral pathogens. It is unknown whether COVID‐19 convalescent plasma (CCP) may contain pathogenic viruses (either newly acquired or reactivated) that are not routinely screened for by blood centers. Methods: The DNA virome was characterized in potential CCP donors ( n  = 30) using viral genome specific PCR primers to identify DNA plasma virome members of the Herpesviridae [Epstein Barr Virus (EBV), cytomegalovirus (CMV), human herpesvirus 6A/B, human herpesvirus 7] and Anelloviridae [Torque teno viruses (TTV), Torque teno mini viruses (TTMV), and Torque teno midi viruses (TTMDV)] families. In addition, the RNA plasma virome was characterized using unbiased metagenomic sequencing. Sequencing was done on a HiSeq2500 using high output mode with a read length of 2X100 bp. The sequencing reads were taxonomically classified using Kraken2. CMV and EBV seroprevalence were evaluated using a chemiluminescent immunoassay. Results: TTV and TTMDV were detected in 12 (40%) and 4 (13%) of the 30 study participants, respectively; TTMDV was always associated with infection with TTV. We did not observe TTMV DNAemia. Despite CMV and EBV seroprevalences of 33.3% and 93.3%, respectively, we did not detect Herpesviridae DNA among the study participants. Metagenomic sequencing did not reveal any human RNA viruses in CCP, including no evidence of circulating SARS‐CoV‐2. Discussion: There was no evidence of pathogenic viruses, whether newly acquired or reactivated, in CCP despite the presence of non‐pathogenic Anelloviridae . These results confirm the growing safety data supporting CCP.